Some q-analogues of Hermite-Hadamard Type Integral Inequalities for the Godunova-Levin and s-Godunova-Levin Class of Functions - Adhikari, Narayan Prasad; Paudyal, Rajendra; Bhatta, Suresh (Journal of Advanced College of Engineering and Management, 2024)
Hermite and Hadamard independently introduced the Herimite-Hadamard inequality for convex functions for the first time. In the recent years ,varieties of extensions were given with the use of convex functions by the several researchers. In this paper we give q- analogue for the variants of Hermite-Hadamard integral inequality for the Godunova-Levin and s-Godunova class of function.